2014
DOI: 10.1186/2049-1891-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduced energy density of close-up diets on dry matter intake, lactation performance and energy balance in multiparous Holstein cows

Abstract: Energy intake prepartum is critically important to health, milk performance, and profitability of dairy cows. The objective of this study was to determine the effect of reduced energy density of close-up diets on dry matter intake (DMI), lactation performance and energy balance (EB) in multiparous Holstein cows which were housed in a free-stall barn and fed for ad libitum intake. Thirty-nine dry cows were blocked and assigned randomly to three groups fed a high energy density diet [HD, n = 13; 6.8 MJ of net en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 26 publications
4
28
0
Order By: Relevance
“…This is in agreement with Huang et al . () who reported that DMI of dairy cows within 5 weeks postpartum decreased by an average of 0.9 kg/day in high energy diets (6.8 MJ/kg) compared to low energy diets (5.4 MJ/kg). The decrease of DMI in high energy diets may be caused by dietary fat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in agreement with Huang et al . () who reported that DMI of dairy cows within 5 weeks postpartum decreased by an average of 0.9 kg/day in high energy diets (6.8 MJ/kg) compared to low energy diets (5.4 MJ/kg). The decrease of DMI in high energy diets may be caused by dietary fat.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports (Huang et al . ; van Knegsel et al . ) reflected that dietary energy content may affect energy metabolism of cows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete details of animal management and diets were the same as our previous research (Huang et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…; Janovick & Drackley ; Huang et al . ) have shown that over‐consumption of energy prepartum often results in a slower increase in DMI postpartum compared with cows which had low energy consumption. These papers focused on the effect of prepartum energy intake on DMI, energy balance, milk performance, body weight (BW) and body condition score (BCS) change, energy metabolism, gluconeogenesis, adipose tissue mobilization or incidence of health diseases.…”
Section: Introductionmentioning
confidence: 99%